Airway inflammation in patients affected by obstructive sleep apnea - Sabato, R.; Guido, P.; Salerno, F.G.; Resta, O.; Spanevello, A.; Foschino Barbaro, M.P. (Monaldi Archives for Chest Disease, 2016)
Obstructive sleep apnea (OSA) is characterised by repetitive episodes of upper airway occlusion during sleep. OSA has been shown to be associated with a variable degree of nasal inflammation, uvula mucosal congestion and airway hyperreactivity. The upper airway inflammation, whose clinical importance is uncertain, is characterised by leukocytes infiltration and interstitial oedema. In addition, recent data has shown the presence of neutrophilic inflammation in the lower airways. The current opinion is that airway inflammation is caused by the local, repeated mechanical trauma related to the intermittent airway occlusion typical of the disease. Another potential mechanism involves the intermittent nocturnal hypoxemia that through the phenomenon of the ischemia- reperfusion injury may induce the production of oxygen free radicals and therefore cause local and systemic inflammation. Finally, a state of low-grade systemic inflammation may be related to obesity per se with the pro-inflammatory mediators synthesised in the visceral adipose cells. Several authors stress the role of circulating and local inflammatory mediators, such as proinflammatory cytokines, exhaled nitric oxide, pentane and 8-isoprostane as the determinants of inflammation in OSA.